REDUCTION IN SPINAL-INDUCED HYPOTENSION WITH ONDANSETRON IN PARTURIENTS UNDERGOING CAESAREAN SECTION. - Neeraj; Kumar, Niraj; Prasad, Sudama; Kumar, Rakesh (Student's Journal of Health Research Africa, 2024)
Background Spinal anesthesia is the predominant technique utilized for caesarean sections, owing to its quick onset, straightforward administration, and efficacy. Objective: The aim is to evaluate how well intravenous ondansetron reduces spinal-induced hypotension in parturients who underwent elective cesarean delivery under spinal anaesthesia. Methods Patna Medical College & Hospital conducted this prospective, randomized, double-blind trial over a 12-month period. Randomized into two groups (n=46 each), ninety-two ASA I/II parturients booked for elective lower segment cesarean delivery under spinal anesthesia were: Group O (ondansetron group): Five minutes before spinal anesthesia, 8 mg of ondansetron intravenously. Group C (Control group) received 10 mL of normal saline intravenuously. Using 2 mL of 0.5% hyperbaric bupivacaine, all patients underwent spinal anesthesia. Baseline and consistent interval documentation of hemodynamic measurements—systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate (HR)—was recorded for thirty minutes following the block. There were reports of hypotension, vasopressors (ephedrine), and side effects included nausea and vomiting. Results The occurrence of hypotension was markedly reduced in Group O (26.1%) in contrast to Group C (63%). The ondansetron group required a much lower overall dose of ephedrine. Moreover, Group O saw a reduced incidence of intraoperative nausea and vomiting. The hemodynamic parameters exhibited greater stability in the ondansetron group during the monitoring period. No negative effects were observed in either group. Conclusion The prophylactic injection of intravenous ondansetron markedly diminishes the occurrence and intensity of spinal-induced hypotension in parturients having cesarean section. Its use also diminishes the necessity for vasopressors and enhances intraoperative mother comfort by alleviating nausea and vomiting. Ondansetron, a secure and easily accessible medication, may be regarded as a beneficial addition in the therapy of spontaneous intracranial hypotension during obstetric anesthesia.